A Hybrid Optimization Approach for Non Linear Function Approximation in High Dimensional Spaces - Achmad Rifai; Sesi Herawani; Mery Windya Pramita (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This paper introduces a hybrid optimization approach that combines genetic algorithms with gradient descent for effective nonlinear function approximation in highdimensional data. Traditional methods struggle with computational efficiency and accuracy in such complex spaces. By integrating genetic algorithms to provide a global search strategy with gradient descent for finetuning, the proposed method achieves faster convergence and improved accuracy. Simulations and case studies demonstrate its effectiveness in applications like data mining, image recognition, and financial modeling.